Unlocking the potential of livestock technologies in Ethiopia: Shifting from individual pieces to optimizing the sum of the parts - Ergano, Kebebe; Duncan, Alan J.; Oosting, Simon J. (International Livestock Research Institute, 2013)
The reasons why farmers are unable to harness the benefits embedded in technologies and take advantage of business opportunities in livestock sector in developing countries remain unresolved. Drawing on insights from innovation systems approaches, this paper assesses innovation constraints, identifies the bottlenecks and missing links in dairy sector and suggests some instruments needed to address the constraints. We find that missing actors, limited capacity of existing actors, inadequate interactions between actors and poor coordination of activities along dairy value chain have been the major reasons for low technology adoption and underdevelopment of dairy subsector in developing countries. Future research should pay attention to designing, prototyping and experimenting with alternative institutional arrangements that can effectively coordinate inputs, services, processes and outputs in livestock value chains.